ปัจจัยที่มีความสัมพันธ์ต่อพฤติกรรมการบริโภคอาหารในผู้ป่วยบาดเจ็บไขสันหลัง - พนอ ทับทิมทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this correlational research were to study the eating behavior and to examine the factors related between level of injury, depression, family relationship, patient’s self-dependence and eating behavior in spinal injury patients. The conceptual framework used in this study was Roy’s adaptation model. The purposive sampling techniques were applied to select the samples, which included 80 patients with spinal injury and age between 18 to 59 years old and received follow up at King Chulalongkorn Memorial Hospital and Phramongkutklao Hospital. The instruments for data collection included a demographic data, the level of spinal injury. The questionnaires included patients’ depression, family relationship, patient’s self-dependence, and the eating behavior. the reliability and Cronbach’ s alpha coefficient of those questionnaires were 0.80, 0.92, 0.89, 0.94 and 0.80 respectively. The Descriptive statistics included frequency, percentage, mean, standard deviation, Chi-Square, Contingency-coefficient and Pearson’s product moment. The major finding was as follow: 1. The spinal injury patients had a good eating behavior scores (X=3.84, SD=.34). 2. The level of injury and patient’s depression level was not related to eating behavior scores in spinal injury patients. 3. Patient’ s self-dependence level had significant correlation with eating behavior scores in the spinal injury patients. (X²= 91.22; P-value.003). 4. Family relationship scores had significant positive correlation with eating behavior scores in spinal injury patients (r= .239; p=0.05).